Comparison of Treatment Response, Survival Profiles, as Well as Safety Profiles Between CalliSpheres® Microsphere Transarterial Chemoembolization and Conventional Transarterial Chemoembolization in Huge Hepatocellular Carcinoma - Duan, Xuhua; Liu, Juanfang; Han, Xinwei; Ren, Jianzhuang; Li, Hao; Li, Fengyao; Ju, Shuguang (Frontiers in Oncology, 2022)
Purpose: CalliSpheres® microspheres (CSM) is the first drug-eluting beads (DEB) developed in China. This study aimed to compare treatment response, survival and safety profiles between DEB transarterial chemoembolization (DEB-TACE) with CSM and conventional TACE (cTACE) in huge hepatocellular carcinoma (HCC) patients. Methods: 71 patients with huge HCC underwent DEB-TACE or cTACE were consecutively enrolled in this retrospective cohort study. Treatment response was assessed at first month (M1), third month (M3) and sixth month (M6) after TACE therapy; progression free survival (PFS) and overall survival (OS) were evaluated; liver function indexes were recorded before TACE operation (M0), at first week (W1), M1 and M6 after TACE therapy; adverse events which occurred after TACE operation were recorded. Results: DEB-TACE presented with higher objective response rate (60.0% vs. 29.7%, P<0.05) and disease control rate (86.7% vs. 59.4%, P<0.05) compared to cTACE at M3. Regarding survival profiles, PFS (median: 3.3 (95%CI 2.8-3.7) vs. 2.1 (95%CI: 1.7-2.5) months) as well as OS (median: 7.8 (95%CI 4.6-11.0) vs. 5.7 (95%CI: 5.0-6.3) months) were longer in DEB-TACE group compared with cTACE group (both P<0.01). Multivariate Cox’s regression further illustrated that DEB-TACE vs cTACE was an independent protective factor for PFS and OS (both P<0.01). As for safety profiles, patients’ liver function injury was reduced in DEB-TACE group compared with cTACE group. The incidence of fever was lower and CINV was less severe in DEB-TACE group compared with cTACE group (both P<0.05), while no difference in occurrence of liver abscess, increase of ascites or moderate pain between two groups was observed. Conclusion: DEB-TACE with CSM presents with better treatment response, survival profiles as well as safety profiles compared to cTACE in treatment for huge HCC patients.